PedsCases - A Learning Module of Neonatology Cases for Medical Students - Peter Gill; Peter MacPherson; Melanie Lewis; Chloe Joynt (Association of American Medical Colleges, 2010)
Abstract This resource is a learning module featuring three multistep cases covering common neonatal presentations that medical students may encounter. The cases are focused on the topics of neonatal jaundice, vomiting in an infant, and copious secretions in a newborn. Each case works through the appropriate management, diagnosis, and treatment of the respective conditions. This resource is a part of PedsCases, a comprehensive web-based educational series that focuses on the core objectives of undergraduate pediatric education with extensive student involvement. PedsCases was created for and by medical students to provide an opportunity for active self-directed learning in pediatrics.